Modeling verbal and Nonverbal Interaction - a Catastrophe Theoretic Contribution to the Intergrammar of Arndt and Janney - Lund, Steffen Nordahl (HERMES - Journal of Language and Communication in Business, 2017)
The article deals with the interpretive framework of Arndt and Janney’s Intergrammar. An intergrative modelisation of verbal, prosodic and kinesic choices in speech is proposed within the methodology of catastrophe theory in order to analyze the dynamics of the functional relationships between these unifying aspects of face-to-face communication.